Case report: Clinical characteristics and Genetical analysis of HSD11B2 in three Chinese children with apparent mineralocorticoid excess: a case series - Ding, Yuan; Cheng, Ming; Cao, Bingyan; Liu, Min; Hu, Xuyun; Wu, Di (Frontiers in Endocrinology, 2025)
BackgroundApparent Mineralocorticoid Excess (AME) is a rare autosomal recessive disorder, characterized by a notably complex diagnostic process. To date, the majority of documented cases have been presented as individual case reports. This article aims to enhance the understanding of the course and prognosis of AME, by detailing the management protocols employed for patients with genetically confirmed diagnoses.MethodsAn analysis comprising three cases and a review of relevant literature were conducted to synthesize the insights and experiences derived from gathering clinical and laboratory data on patients.ResultsAll three patients were born to non-consanguineous parents, were small for gestational age and exhibited severe hypokalemia, metabolic alkalosis, hypertension, nephrocalcinosis, and hypercalciuria. The glomerular filtration rate was normal in all cases. One patient experienced complications related to hypertension. Genetic analysis revealed biallelic recessive variations in the HSD11B2 gene in all three patients. Treatment with oral spironolactone and potassium chloride resulted in the normalization of both blood pressure and serum potassium levels in all patients.ConclusionThis study presents the diagnostic and treatment experiences of three Chinese pediatric patients with AME type I. Through our analysis, four novel variants of the HSD11B2 gene were identified, thereby enhancing the genotype-phenotype spectrum associated with AME. Early genetic testing in patients suspected of having AME is beneficial for facilitating prompt diagnosis and the implementation of standardized treatment protocols. Such measures are essential for the prevention or mitigation of target organ damage, as well as for the reduction of associated morbidity and mortality